Promoting shared meanings in group memberships: a social identity approach to leadership in sport - Slater, M. J.; Coffee, P.; Barker, J. B.; Evans, A. L. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
The purpose of this review is to demonstrate the applicability of a social identity approach to leadership in sporting contexts. A social identity approach to leadership contends that leaders and group members are connected through feeling a sense of belonging and emotional attachment to their group. The present review (1) outlines the theoretical underpinnings of social identity theory, (2) reflects on the four principles of social identity leadership and applies them to sport, (3) contrasts social identity leadership with current leadership theories, and (4) provides suggestions for future research investigating a social identity approach to leadership in sport. Accordingly, the review illustrates how an appreciation of the social context and group members` values allow leaders to mobilise - enlist the motivation and abilities of - athletes to achieve the leader`s vision. A social identity approach to leadership has the potential to extend understanding of leadership in sport by emphasising the role of groups and context in leadership.